Asbestos risk in archaeology - Bianchi, Claudio; Bianchi, Tommaso (La Medicina del Lavoro, 2014)
Asbestos has been used since prehistoric times (1). The most ancient relics date back to about 4,000 BC; in the Savo area, south-eastern Finland, asbestos (antophyllite) was used in making pottery (4). Asbestos clothes found in some tombs of several sites in Thailand date back to the Neolithic and Bronze Ages (2). ...